Analysis Of The Correlation Between Reading Habits And Ability To Read Comprehension In Class Xi Students Of Smk PP Rea Timur Polewali Mandar Polewali Mandar - Sapiah, Siiti; S. Abu Alama (International Journal of Education, Vocational and Social Science, 2022)
This study aims to describe whether or not there is a relationship between reading habits and reading comprehension ability in class IX students of SMK PP Rea Timur Polewali Mandar. This study is a descriptive study using correlational analysis methods. The population in this study was 74 students and sample study. In this study data was collected from two sources, namely the questionnaire value from the results of the reading habit questionnaire test and the value of reading comprehension ability from the results of the comprehension reading ability test. Data obtained in the form of primary data using a quantitative descriptive approach with an objective process and analyzing data. The results of the analysis in this study indicate that the relationship between reading habits and reading comprehension ability of class XI students at SMK PP Rea Timur Polewali Mandar has a positive correlation. In this study, it is hoped that the readers and writers themselves will be able to further improve their reading skills.